The restoration of REST inhibits reactivity of Down syndrome iPSC-derived astrocytes - Huang, Tan; Fakurazi, Sharida; Cheah, Pike-See; Ling, King-Hwa (Frontiers in Molecular Neuroscience, 2025)
IntroductionAccumulating evidence indicates that the increased presence of astrocytes is fundamentally linked to the neurological dysfunctions observed in individuals with Down syndrome (DS). REST (RE1-silencing transcription factor), as a chromatin modifier, regulates 15,450 genes in humans. REST is a key regulatory element that governs astrocyte differentiation, development, and the maintenance of their physiological functions. The downregulation of REST may disrupt the homeostatic balance of astrocytes in DS.MethodsThis study aims to elucidate the role of REST in DS-astrocytes through comprehensive transcriptomic analysis and experimental validation.ResultsTranscriptomic analysis identified that REST-targeted differentially expressed genes (DEGs) in DS astrocytes are enriched in pathways associated with inflammatory response. Notably, our findings in astrocytes derived from DS human induced pluripotent stem cells (hiPSCs) show that the loss of nucleus REST leads to an upregulation of inflammatory mediators and markers indicative of the presence of reactive astrocytes. Lithium treatment, which restored nucleus REST in trisomic astrocytes, significantly suppressed the expression of these inflammatory mediators and reactive astrocyte markers.DiscussionThese findings suggest that REST is pivotal in modulating astrocyte functionality and reactivity in DS. The loss of REST in DS-astrocytes prompts the formation of reactive astrocytes, thereby compromising central nervous system homeostasis. Lithium treatment possesses the potential to rescue astrocyte reactivity in DS by restoring nucleus REST expression.